Acute decrease of urine calcium by amiloride in healthy volunteers under high-sodium diet. Issue 2 (29th April 2021) - Harmacek, Dusan; Blanchard, Anne; Wuerzner, Gregoire; Maillard, Marc; Jeunemaitre, Xavier; Azizi, Michel; Bonny, Olivier
Abstract: Background: Amiloride is a competitive blocker of the epithelial sodium (Na) channel in the renal collecting duct. It is a less potent diuretic than thiazides or loop diuretics, but is often used in association with its potassium (K)-sparing profile. Whether amiloride has a hypocalciuric effect similar to thiazides remains unclear. Animal studies and experiments on cell lines suggested that amiloride increases calcium (Ca) reabsorption in the distal nephron, but human studies are scarce. Methods: We performed a post hoc analysis of a study with 48 healthy males (mean ± standard deviation age, 23.2 ± 3.9 years) who were assigned to a high-Na/low-K diet for 7 days before receiving 20 mg of amiloride orally. Urinary excretions of electrolytes were measured at 3 and 6 h afterwards; we calculated the relative changes in urinary excretion rates after amiloride administration. Results: The high-Na/low-K diet led to an expected suppression of plasma renin and aldosterone. Amiloride showed a mild natriuretic effect associated with a decreased kaliuresis. Urinary Ca excretion dropped substantially (by 80%) 3 h after amiloride administration and remained low at the sixth hour. At the same time, fractional excretion of lithium decreased by a third, reflecting an increased proximal tubular reabsorption. Conclusions: During a high-Na/low-K diet, amiloride had a strong acute hypocalciuric effect, most probably mediated by increased proximal Ca reabsorption, even though a distal effect cannot be excluded. Further studies should establish if chronic amiloride or combined amiloride/thiazide treatment may decrease calciuria more efficiently and be useful in preventing kidney stones.